Language and Stylistic Aspects of Karel Capek’s Journalistic Writing: An Analysis of "Hovory s T. G. Masarykem" through the Method of Textual Linguistics - Mecco, Martina (2022)
The present contribution focuses on Karel Capek’s Hovory s T.G. Masarykem to analyse its intrinsic structure byapplying František Daneš’ model of thematic progressions (TP), ie. the choice and ordering of utterance themes,their mutual concatenation and hierarchy, as well as their relation to the hyperthemes of the superior text unit (suchas paragraph, chapter, etc.), to the whole text, and to the situation. Thematic progression might be viewed as theskeleton of the plot. This contribution aims to identify the thematic progression patterns (simple linear, constant,with derived themes), in particular in the third part, focused on Masaryk’s thinking. Thanks to the identificatioof the thematic progressions, it is possible to ascertain the communicative intention of the author and to point outsome formal aspects. Differently from the first two parts, in which the style is mainly narrative, in the third one theintention of Capek is to reproduce the style of the president’s speeches. Putting in writing Masaryk’s thoughts, Capekpreserves the oral dimension and the stylistic originality of the speaker. Moreover, Masaryk himself contributed tothe editing of the Hovory.
Keywords: Capek, Karel; Masaryk,Tomáš Garrigue